A NEWLY RECORDED SPECIES Galium asperifolium (RUBIACEAE) FOR THE FLORA OF VIETNAM - The Bach, Tran; Minh Tam, Ha; Trong Tri, Nguyen; Thi Nhu Binh, Dao; Huu Duy, Hoang; Hoang Tuan, Cao; Thu Ha, Bui (HNUE Journal of Science: Journal of Natural Sciences, 2025)
Plant specimens coded as LC202421 at Hanoi Herbarium, were identified as Galium asperifolium Wall. This is a newly recorded species for the flora of Vietnam. The morphological comparison method was applied appropriately in the study. The genus Galium in Vietnam includes 3 updated species: G. aparine L. auct. non L.: P. H. Ho, G. asperifolium Wall., and G. rotundifolium L. G. asperifolium Wall. is distinguished from the two other species by the characteristic of “basal vein 1”. An identification key for the species of Galium currently known in Vietnam was established. G. asperifolium in Vietnam was described in detail, including its scientific name, synonyms, morphological and ecological characteristics, flower and fruit season, distribution, research sampling, and various images.